Acute recurrent pancreatitis curtaining an intraductal papillary mucinous tumor of the pancreas - Retter, Jürgen; Dinter, Dietmar; Bersch, Claus; Singer, Manfred V.; Löhr, J.-Matthias (Journal of gastrointestinal and liver diseases, 2007)
Intraductal papillary mucinous tumor (IPMN) of the pancreas is a rare pancreatic tumor characterized by intraductal proliferation of mucin producing cells with hypersecretion of mucin that leads to cystic dilatation of the involved ducts. The usual clinical presentation is recurrent episodes of pancreatitis due to hypersecretion of mucin and temporary obstruction of the main pancreatic duct.